Evaluation of the secondary students’ attitudes towards studying and learning science and mathematics, and their impact on learning in the two schools in the Northern Finland - Tomperi, P. (Päivi) (Redfame Publishing, 2020)
Abstract The objective of this study was to examine secondary students’ attitudes towards studying and learning science and mathematics, and how the attitude constructs were linked in students’ responses. As a result of the hierarchical cluster analysis, six classes were obtained. Based on Cronbach’s alpha values, two clusters were excluded from the final model leaving the classes which were named as motivation, the nature of the classroom environment, enjoyment, and achievement. In this classification attitudes of parents were related to motivation, attitudes of friends to enjoyment, perception of the teacher to the nature of the classroom environment, and anxiety and fear of failure to achievement. To determine factors affecting students’ prior learning in different disciplines of natural sciences, mathematics, and IT, stepwise multiple regression was carried out with self-estimated skill score as the dependent variable to discover which items were related to learning in the four classes of the model. The main predictor for achievement was item “physics is more difficult for me than for many of my classmates” (adjusted R² = 29.6 %) and for motivation “my parents are proud of my achievements in science and math” (adjusted R² = 19.9 %). One item showed gender difference with medium effect size.